Outlander : Season three, Disc one - Balfe, Caitriona; Moore, Ronald D.; Brown, David; Heughan, Sam, 1980-; Menzies, Tobias, 1974-; Weber, Stanley, 1986-; Lewis, Gary, 1958-; McTavish, Graham; Lacroix, Duncan; Verbeek, Lotte, 1982-; Walters, Stephen (Stephen Martin); O'Rourke, Grant; et al. (Culver City, California Sony Pictures Home Entertainment, 2018)
Follows the story of Claire Randall, a married combat nurse from 1945 who is mysteriously swept back in time to 1743, where she is immediately thrown into an unknown world where her life is threatened. When she is forced to marry Jamie Fraser, a chivalrous and romantic young Scottish warrior, a passionate relationship is ignited that tears Claire's heart between two vastly different men in two irreconcilable lives. In Season 2, Claire and Jamie arrive in France, hell-bent on infiltrating the Jacobite rebellion led by Prince Charles Stuart and stopping the battle of Culloden. With the help of Jamie's cousin, they are thrown into the lavish world of French society, where intrigue and parties are abundant but political gain proves far less fruitful. Altering the course of history presents challenges that begin to weigh on the very fabric of their relationship - but, armed with the knowledge of what lies ahead, Claire and Jamie must race to prevent a doomed Highland uprising and the extinction of Scottish life as they know it.
The battle joined -- Surrender -- All debts paid.
Complete Season 3 contained on 5 disc set.
Based on the book series by Diana Gabaldon.
Originally aired on television in 2017.
Anamorphic widescreen (1.78:1).
Sam Heughan, Caitriona Balfe, Tobias Menzies, Duncan Lacroix, Stanley Weber, Graham McTavish, Grant O'Rourke, Stephen Walters, Gary Lewis, Lotte Verbeek.
Rating: TVMA.
Keywords: Gabaldon, Diana -- Television adaptations; Nurses -- Great Britain -- Drama; Time travel -- Drama; Outlaws -- Scotland -- Drama; Man-woman relationships -- Drama; Scotland -- Drama; Great Britain; Action and adventure television programs; Drama; Fantasy television programs; Feature films; Fiction television programs; Historical television programs; Television adaptations; Television programs; Television series; Video recordings for the hearing impaired